Pirates, hackers, and nomads: Politics in the radical transparency age - Vargas Rodríguez, Manfred (2012)
The aim of this essay is to describe and explain the purpose and modus operandi of three different organizations currently fighting to implement radical transparency in politics: Wikileaks, Anonymous and the Pirate Parties. Special attention is given to the ways in which these organizations utilize the Internet and other technological tools in order to spread their message and present their demands; as well as exploring the differences between these organizations when it comes to dealing with the State and the political system. It is concluded that, even though Wikileaks and Anonymous have accomplished an important media presence, the Pirate Parties are best positioned to achieve reforms in government that will lead to greater transparency.